Current evidence supporting obstetric fistula prevention strategies in sub Saharan Africa: a systematic review of the literature. - (:unkn) unknown (My University, 2014)
Obstetric fistula has been eliminated in developed countries, but remains highly prevalent in sub-Saharan Africa. The End fistula campaign is the first concerted effort to eradicate the disease. The objective of this review is to retrieve and link available evidence to obstetric fistula prevention strategies in sub-Saharan Africa, since the campaign began. We searched databases for original research on obstetric fistula prevention. Fifteen articles meeting inclusion criteria were assessed for quality, and data extraction was performed. Grey literature provided context. Evidences from the articles were linked to prevention strategies retrieved from grey literature. The strategies were classified using an innovative target-focused method. Gaps in the literature show the need for fistula prevention research to aim at systematically measuring incidence and prevalence of the disease, identify the most effective and cost-effective strategies for fistula prevention and utilise innovative tools to measure impact of strategies in order to ensure eradication of fistula.
Keywords: African Research